ANALYZING AN ORAL NARRATIVE USING DISCOURSE ANALYSIS TOOLS - Syam Tenrisanna Andi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2016)
Discourse analysis tools are important for language teachers as applied linguistics has always taken elements from different fields of study. To analyze a spoken text we have to divide it into its idea units. Identifying-classifying idea units are included, (1) organizational pattern of oral texts; (2) formulaic expressions; (3) use of single adjectives; (4) subordination; (5) intonation; (6) center of interest; and (7) perturbations of oral narrative. Oral narratives are composed of chronological elements such as abstract, orientation, and resolution. The writer used transcript of oral text to be analyzed.